Unactivated Norbornenes in [3+2] Cycloadditions: Remarkably Stereocon- trolled Entry into Norbornane-Fused-Spirooxindolopyrrolidines, Spiro-1,3- in- dandionolylpyrrolidines and Spirooxindolopyrrolizidines - Rajkumar, V.; Aslam, N.A.; Reddy, C.; Babu, S.A. (Theime, 2011)
1,3-dipolar cycloaddition reactions of azomethine ylides with unactivated norbornene dipolarophiles and a highly diastereoselective synthesis of the novel norbornane-fused spirooxindolopyrrolidines, spiroacenaphthylenolylpyrrolidines, spiro-1,3-indandionolylpyrrolidines, and spirooxindolopyrrolizidines having an array of stereocenters are reported. The stereoselective synthesis of spirooxindolopyrrolizidines with eight stereocenters was demonstrated. Single-crystal X-ray structural analyses were performed to unambiguously establish the structure and stereochemistry of the key products.
Keywords: 1,3-dipolar cycloaddition; oxindoles; spiro compounds